(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2020)
In this paper an analysis of the processes of adaptation of the Greek alphabet to four different languages of the Ancient Mediterranean is offered; Oenotrian (a Sabellian dialect), Iberian, Oscan and Gaulish. In each case the author shows how the process of adaptation was, and also the chronology of the use of the script and some palaeographic features. In general terms, these four alphabets are rather ways of writing a local language by means of Greek letters than a specific creation of a script as a sign of identity.